2017
DOI: 10.14258/turczaninowia.20.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Spore morphology of Onychium ipii Ching (Pteridoideae, Pteridaceae)

Abstract: Summary. The ultrastructure of the spore surface of Onychium ipii Ching (Pteridoideae, Pteridaceae) was investigated by using of scanning electron microscopy. Spores of Onychium ipii are trilete, tetrahedral, with hemispherical distal side and convex proximal one. Equatorial diameter 42.4-48.1 μm, polar axis 35.7-40.6 μm. Distal and proximal sides are separated by an equatorial flange, which protrudes on 4.3-4.8 μm all around the spore. Tubercles of different size form the interrupt "laesura lips" situated on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…emodi), terminate more abruptly into a usually long apical segment; frond apex suddenly reduced to an abrupt, usually long drooping terminal segment; lamina unipinnate, oblong, lanceolate (Figure 6f); sori located on the overall both margins of lamina, spore trilete, triangular with laesura in proximal view, spheroidal, hemispherical at distal view with spinulose, tuberculate surface, equatorial view with equilateral flange at the middle, size 36-45 Â 37-48 μm, surface cristate, granulose, tuberculate at proximal view, granulose, cristate at distal view (Figure 10a-c). The spore morphology of Cheilanthoideae and Pteridoideae (Pteridaceae) species observed under SEM represents variations in size, shape, aperture and surface ornamentation, as described in many previous studies (Giacosa, Morbelli, & Giudice, 2004;Makgomol, 2006;Nayar & Devi, 1966, 1967Vaganov, Gureyeva, Shmakov, Kuznetsov, & Romanets, 2018a, 2018b et al ( ) and Vaganov et al (2017et al ( , 2020. The spores of Pteris cretica subsp.…”
Section: Onychium Vermaementioning
confidence: 58%
See 1 more Smart Citation
“…emodi), terminate more abruptly into a usually long apical segment; frond apex suddenly reduced to an abrupt, usually long drooping terminal segment; lamina unipinnate, oblong, lanceolate (Figure 6f); sori located on the overall both margins of lamina, spore trilete, triangular with laesura in proximal view, spheroidal, hemispherical at distal view with spinulose, tuberculate surface, equatorial view with equilateral flange at the middle, size 36-45 Â 37-48 μm, surface cristate, granulose, tuberculate at proximal view, granulose, cristate at distal view (Figure 10a-c). The spore morphology of Cheilanthoideae and Pteridoideae (Pteridaceae) species observed under SEM represents variations in size, shape, aperture and surface ornamentation, as described in many previous studies (Giacosa, Morbelli, & Giudice, 2004;Makgomol, 2006;Nayar & Devi, 1966, 1967Vaganov, Gureyeva, Shmakov, Kuznetsov, & Romanets, 2018a, 2018b et al ( ) and Vaganov et al (2017et al ( , 2020. The spores of Pteris cretica subsp.…”
Section: Onychium Vermaementioning
confidence: 58%
“…Duthie (1898); Hope (1896) documented nine taxa of Pteridaceae from northern areas, Pakistan;Stewart (1972) documented 6 genera with 22 taxa of Cheilanthoideae and Pteridoideae from Pakistan; Lee, Oh, and Lee (1990) documented the taxonomy and spore morphology of Pteridaceae from Korea; Nakaike andMalik (1992, 1993) reported 4 genera with 11 taxa of Cheilanthoideae and Pteridoideae from various localities of Azad Jammu and Kashmir, Gilgit-Baltistan, Hazara and Malakand divisions; Morbelli, Ponce, MacLuf, and Piñeiro (2001) documented the spore morphology of Notholaena species through scanning electron microscopy from South America. Sen and Mukhopadhay (2011) documented the spore morphology of five Species of Cheilanthes through LM and SEM from India; Fraser-Jenkins (2014) and Fraser-Jenkins et al (2016) documented 8 genera with 26 taxa of Cheilanthoideae and Pteridoideae, with a comprehensive specimen based inventory of the pteridophytes of Pakistan; Gul, Alam, Ahmad, and Irfan (2016) reported 5 genera with 18 taxa of Cheilanthoideae and Pteridoideae from district Mansehra, Pakistan; Chao, Mustapeng, Chen, and Chiou (2017) evaluated the spore morphology of Pteris borneensis, P. decrescens and P. parviloba, Pteridaceae through SEM from Borneo Island; Masoumi, Ghasempour, and Sobhi (2017) documented the spore morphology and developmental stages of Cheilanthes persica from Kermanshah, Iran; Vaganov, Gureyeva, Kuznetsov, Shmakov, and Romanets (2017) documented the spore morphology through SEM of Onychium ippi, Pteridoideae, Pteridaceae from China; Chao and Huang (2018) documented the spore morphology through SEM of 57 species of pteridaceae; Shah, Çelik, Ahmad, et al (2019)…”
mentioning
confidence: 99%
“…Flora of China includes 13 species (Zhang et al, 2013). Our previous studies of spores of some Pteridaceae groups are shown that spore morphology studied using SEM-method and molecular-phylogenetic results are congruent for different genera such as Onichium (Vaganov et al, 2017a), Pityrogramma (Vaganov et al, 2017b), Vaginularia (Vaganov et al, 2017c). Morphology of spores is very important for systematics of subfamilies Pteridoideae (Kuznetsov, 2014), Cryptogrammoideae (Vaganov, 2016) and Ceratopteridoideae (Vaganov et al, 2017c).…”
mentioning
confidence: 95%